2009
DOI: 10.1680/coma.2009.162.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The engineering properties of Victorian structural wrought iron

Abstract: This paper presents results, which are of general interest and relevance to the structural engineering community, from a comprehensive investigation of the mechanical properties of the wrought iron from a bridge in mid-Wales, together with data from tests over the last 125 years on wrought iron from various locations. The paper discusses the variability of wrought iron in terms of material from a single source and from different sources throughout the UK. It is shown that wrought iron is a very variable materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The tension, compression and Charpy impact tests have been described elsewhere. 1 The remaining tests will be described below.…”
Section: Test Methods and Environmental Conditioningmentioning
confidence: 99%
“…The tension, compression and Charpy impact tests have been described elsewhere. 1 The remaining tests will be described below.…”
Section: Test Methods and Environmental Conditioningmentioning
confidence: 99%
“…Assessment of Victorian wrought iron and its engineering properties has been given by Moy et al . ( 2004 ) and Moy et al . ( 2009 ).…”
Section: Types Of Metallic Materials and Structures Needing Rehabilitmentioning
confidence: 96%
“…Due to the presence of large slag inclusions parallel to rolling direction that were generated during fabrication of puddle iron plates, yield stress fy is typically lower in the transversal direction [42,43]. Based on a previous study by the authors [9], a significant amount of longitudinal non-metallic inclusions was observed on micrographs of puddle iron plates from Redondela bridge.…”
Section: Calibration Of Local Fe Modelmentioning
confidence: 99%